ENT 530 Social Media Portfolio / Nur Anis Samsul Anwar - Samsul Anwar, Nur Anis (2019)
The business I have chosen is under food and beverages. The product is namely Sapid Smores. The Sapid Smores is mainly product of butterscotch cookies layered with chocolate sauce and burned marshmallow at the top and a little bit of salted caramel sauce. The founder of this business is Ain Najiha bt Mohamad Nor. Basically, they promote their product through social media such as Whatsapp, Facebook and lnstagram. They also provide for Cash on delivery. In order to widen their business, they offered public to join as an agent or dropship. So, for this assignment I am interested with their business and already registed as one of their agent. I will be an agent for area Puncak Alam. For marketing purposes, Sapid Smores strategy is to emphazise the quality and price of product and services. The Sapid Smores offer the affordable prices because many people in Puncak Alam is UITM students. I have use social media platform by utilizing Facebook (FB). For three months, I have successfully achieved the target sales which is RMlSO. I have registered this business under SSM using the names NUR ANIS BINTI SAMSUL ANWAR.